Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1097/md.0000000000017297
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miR-21 levels in hypertensive patients with asymptomatic organ damage

Abstract: As a modifiable risk factor for cardiovascular disease, presence of hypertension (HT) necessitates the awareness of asymptomatic organ damage (AOD). The aim of this study was to measure plasma micro RNA-21 (miR-21) and the parameters that reflect AOD such as carotid intima-media thickness (CIMT), microalbuminuria (MAU) in hypertensive patients compared with healthy controls. In addition, the aim of this study was to evaluate plasma miR-21 levels in HT patients with AOD.This study was designed as a cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 16 publications
0
8
1
3
Order By: Relevance
“…Furthermore, the significant relationship between miR-30a-5p expression and screen-detected and known HPT was demonstrated. Several studies have reported on a number of dysregulated miRNAs in HPT using different tissues, but results remain inconsistent (21)(22)(23)(24)(25). A study similar to ours reported 27 dysregulated miRNAs in a sample of 13 individuals with HPT (21), although the miRNAs were not similar to ours.…”
Section: Discussioncontrasting
confidence: 59%
“…Furthermore, the significant relationship between miR-30a-5p expression and screen-detected and known HPT was demonstrated. Several studies have reported on a number of dysregulated miRNAs in HPT using different tissues, but results remain inconsistent (21)(22)(23)(24)(25). A study similar to ours reported 27 dysregulated miRNAs in a sample of 13 individuals with HPT (21), although the miRNAs were not similar to ours.…”
Section: Discussioncontrasting
confidence: 59%
“…In our previous study of 52 controls and 51 HT patients under follow-up in the Cappadocia cohort, we investigated the place of miRNA 4516, miRNA 181a, miRNA 24, and miRNA 145 in the pathogenesis of essential HT, and showed that a decrease in miRNA 145 and an increase in miRNA 4516 may be involved [ 9 ]. In addition to examining the role of miRNAs in the pathogenesis of essential HT, studies have also investigated their relationship with end-organ damage [ 11 , 12 , 25 ]. Numerous studies have particularly evaluated the role of miRNA 21 in the pathogenesis of essential HT and its relationship with end-organ damage [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yıldırım et al. similarly investigated 32 HT and 32 healthy controls and showed that miRNA 21 is associated with asymptomatic organ damage in the hypertensive population [ 12 ]. In their experimental study, Chen et al.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst the relationship between expression of these two novel miRNAs and BP variables or HPT status cannot be directly compared to similar studies (as our findings are novel), differential expression of miRNAs in HPT has been previously reported [5,13] and expression of miRNAs has also been related to BP parameters. For instance, one study showed a significant correlation between SBP and the expression of miR-21, miR-126 and miR-34a has been reported, whilst miR-146a expression was correlated with SBP and DBP [23].…”
Section: Discussionmentioning
confidence: 54%
“…Using small RNA sequencing techniques, epigenome studies continue to describe novel miRNAs in various body tissues and disease conditions [ 3 , 4 ]. These miRNAs are 18–22 nucleotides long [ 5 ] and are involved in the regulation of gene expression at the post transcription level, either through targeted messenger RNA (mRNA) degradation or inhibition of translation [ 3 , 6 ]. As such, they have a crucial role in maintaining the homeostatic balance of the human body’s processes and dysregulations in their expression may be related to disease processes [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%